THE MONETARY REGIMES AND THE INFLATION DEVELOPMENTS IN THE CENTRAL AND EASTERN EUROPEAN COUNTRIES - Magdalena RADULESCU; Doina Elena DASCALU (Buletin ştiinţific: Universitatea din Piteşti. Seria Ştiinţe Economice, 2016)
This paper aims to presents some considerations regarding some specific monetary regimes adopted in the Central and eastern European countries and the developments of the inflation rate in the frame of these monetary regimes (namely the inflation targeting regime and the Monetary Council regime). The analysis covers both the EU accession moments in 2004 and 2007 and the crisis period started in 2008.